2022
DOI: 10.1055/s-0042-1748899
|View full text |Cite
|
Sign up to set email alerts
|

Metal Artifact Reduction Dual-Energy CT as an Accurate and Reliable Method for Measuring Total Knee Arthroplasty Femoral Component Rotation Compared to Conventional CT

Abstract: This article determines the accuracy and reliability of dual-energy computed tomography (DECT) with metal artifact reduction (MAR) in the evaluation of femoral component rotation after total knee arthroplasty (TKA), in comparison with conventional CT images. A total of 49 patients (mean age, 69 years; 42 women) who underwent TKA between January 2019 and March 2020 were retrospectively enrolled. Femoral component rotation, including the anatomic and surgical transepicondylar axes, was evaluated with preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…All orthopedic surgeons (X.X., X.X., and X.X.) participating in the surgical procedures received training on the Depuy Attune Knee Implant system and had prior experience with the system before this study commenced [12].…”
Section: Surgical Technique and Postoperative Carementioning
confidence: 99%
“…All orthopedic surgeons (X.X., X.X., and X.X.) participating in the surgical procedures received training on the Depuy Attune Knee Implant system and had prior experience with the system before this study commenced [12].…”
Section: Surgical Technique and Postoperative Carementioning
confidence: 99%
“…Previous studies reported that DECT reduced metal artifacts on spine implants, implants for fractures, and hip and knee prostheses [ 40 , 41 , 42 , 50 , 51 , 52 ]. However, there is no generalized optimal kV for metal implants, which may be attributed to differences in metal alloys, the size, shape, and geometry of the implant, the body region, and the acquisition parameters used [ 31 ].…”
Section: Metal Artifact Reduction Strategiesmentioning
confidence: 99%